2000
DOI: 10.1377/hlthaff.19.3.158
|View full text |Cite
|
Sign up to set email alerts
|

Health Plan Switching: Choice Or Circumstance?

Abstract: Data from the Community Tracking Study give a glimpse of who among the privately insured are likely to switch plans, and why.b y P e t e r J. Cu n n i n g h a m a n d L i n d a K o h n C h a n g i n g h e a l t h p l a n s may be beneficial to the extent that it results from consumers' decisions and preferences about what type of health plan best suits their health care needs. On the other hand, consumers today are not only choosing a plan to finance the use of services, but within that decision are also choos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 1 publication
2
53
0
Order By: Relevance
“…3 Our findings of reduced prevention, at least for mammograms, and increased testing expenditures among the newly insured are consistent with our hypotheses and the limited continuity literature. 15,16,24 These previous studies examined immunization status in children in a continuity clinic, 15 recall by Norwegian general practitioners about their testing behavior with patients with more or less continuity, 24 and self-report on prevention by respondents with and without a usual source of care.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…3 Our findings of reduced prevention, at least for mammograms, and increased testing expenditures among the newly insured are consistent with our hypotheses and the limited continuity literature. 15,16,24 These previous studies examined immunization status in children in a continuity clinic, 15 recall by Norwegian general practitioners about their testing behavior with patients with more or less continuity, 24 and self-report on prevention by respondents with and without a usual source of care.…”
Section: Discussionsupporting
confidence: 88%
“…1,2 Data from a 1996-1997 national survey suggests that 17% of privately insured persons changed their health plan in the year before the survey, most of them involuntarily. 3 Forced discontinuity associated with health plan changes is associated with reduced levels of patient satisfaction. 4 There has also been anecdotal concern that changes in health insurance might disrupt care and adversely affect outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The Community Tracking Survey found that among individuals switching private insurance, over 75% was due to employer plan cancellations or a job change, and fewer than 10% switched insurance to obtain Bbetter services^such as preferred doctors. 6,24,25 More importantly, our sensitivity analyses of alternative groups designed to exclude those with potentially endogenous motivations for switching were robust.…”
Section: Discussionmentioning
confidence: 90%
“…For example, on the exchanges, individuals can change plans during the annual open enrollment process, and thus changes in premiums, coverage generosity, and individual health status may lead individuals to switch plans each year. While competition is thought to result in lower prices and improved quality of care, [2][3][4][5][6][7] it is also likely to lead to increased rates of switching among private plans as well as among private insurers participating in Medicaid as enrollees choose among plans. 3,8 The implications of plan switching with respect to health care use and the stability of patient-physician relationships may be a meaningful consideration in this environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation